Light-moisture dual-curing underwater epoxy coating with self-repairing function as well as preparation method and construction method of light-moisture dual-curing underwater epoxy coating
By combining a light-wet dual-curing mechanism with dynamically disulfide bond-modified polysulfide rubber, the problems of insufficient curing speed and depth, self-healing ability and comprehensive performance of underwater epoxy coatings are solved, achieving rapid curing, self-healing, high adhesion and hydrophobicity, which is suitable for the protection of marine engineering structures.
Patent Information
- Application Number
- CN202511472052.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-12-12
AI Technical Summary
Existing underwater epoxy coatings are inadequate in terms of curing speed and depth, self-healing ability, heat resistance, and overall performance, making it difficult to meet the needs for rapid underwater repair and long-term protection.
Employing a light-moisture dual-curing mechanism, this method introduces dynamically disulfide bond-modified polysulfide rubber and boron nitride nanosheets/silicon carbide nanowire hybrid fillers, combined with ultraviolet light and moisture curing, to achieve rapid surface curing and deep cross-linking of the coating, thereby endowing the coating with self-healing ability and high adhesion.
It achieves rapid curing (surface drying within 30 seconds) and deep curing (complete cross-linking within 4 hours) of the coating, and has significant self-healing function, excellent underwater adhesion, good thermal conductivity and hydrophobicity, which significantly improves the protective performance of marine engineering structures.
Smart Images

Figure IMAGE_F1D3C8B0-91A0-4226-8723-DBA1FDB130F5
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a light-wet dual-curing underwater epoxy coating with self-healing function, as well as its preparation and application methods. Background Technology
[0002] Marine engineering structures, such as oil drilling platforms, subsea oil and gas pipelines, cross-sea bridge foundations, and port facilities, operate in harsh marine environments for extended periods, facing severe corrosion challenges. The maintenance and protection of underwater structures has always been a challenging engineering problem. Epoxy resin, due to its excellent adhesion, chemical resistance, and mechanical properties, is one of the commonly used material systems for underwater protection and repair. However, existing underwater epoxy coatings still face many technical bottlenecks: (1) The contradiction between curing speed and curing depth: Traditional wet curing systems require several hours to complete deep curing, which is difficult to meet the needs of rapid underwater repair (such as CN106752689A). (2) Lack of effective self-healing ability: The coating cannot repair itself after it is damaged, which leads to the penetration of corrosive media (such as CN108250910A). (3) Insufficient heat resistance and overall performance: The high temperature environment in the deep sea can easily cause the coating to soften (e.g., CN104745046A). While the latest existing technologies have introduced graphene (CN108192471A) or graphene oxide (CN108250910A) to improve performance, the synergistic problem of dynamic self-healing and rapid curing remains unresolved. Therefore, developing an underwater epoxy coating capable of rapid, deep curing underwater, while simultaneously imparting excellent self-healing capabilities and possessing high underwater adhesion, good heat resistance, and durability, is of significant theoretical and practical value for ensuring the safety and durability of marine engineering structures. Summary of the Invention
[0003] This invention addresses the shortcomings of existing underwater epoxy coatings in terms of curing efficiency, self-healing ability, and overall protective performance by providing a light-wet dual-curing underwater epoxy coating with self-healing capabilities, along with its preparation and application methods. This epoxy coating is suitable for in-situ bonding, rapid repair, and long-term corrosion protection and reinforcement of marine engineering metal structures (such as watertight sleeves, subsea pipelines, and offshore platform pile foundations) in humid or underwater environments.
[0004] In a first aspect, the present invention provides a light-wet dual-curing underwater epoxy coating with self-healing function, which is achieved by the following technical solution.
[0005] A self-healing, light-wet dual-curing underwater epoxy coating comprises component A and component B, wherein the mass ratio of component A to component B is (1.5-3.5):1; Component A comprises the following raw materials in parts by weight: Bisphenol F type epoxy resin: 100 parts; Dynamic disulfide bond modified polysulfide rubber: 20-30 parts; Boron nitride nanosheets and silicon carbide nanowire hybrid filler: 10-20 parts; Photoinitiator: 3-5 parts; Silane coupling agent: 2-4 parts; Component B comprises the following raw materials in parts by weight: Moisture-curing polyetheramine: 50-70 parts; Boron ester crosslinking agent: 10-15 parts; Hydrophobically modified graphene oxide: 5-10 parts.
[0006] Furthermore, the epoxy value of the bisphenol F type epoxy resin is 0.53-0.58 g / eq.
[0007] Furthermore, the sulfur content of the dynamically disulfide bond modified polysulfide rubber is 15-20%; the preparation method of the dynamically disulfide bond modified polysulfide rubber is as follows: liquid polysulfide rubber is mixed with 4,4'-diaminodiphenyl disulfide in a molar ratio of 1:(1~2), and reacted at 60-80℃ for 2~6 hours to generate a prepolymer containing dynamic disulfide bonds.
[0008] Furthermore, the liquid polysulfide rubber selected is JLY-124.
[0009] Furthermore, the preparation method of the boron nitride nanosheets and silicon carbide nanowire hybrid filler is as follows: boron nitride nanosheets and silicon carbide nanowires are dispersed in ethanol at a mass ratio of 1:2, ultrasonically treated for 2-4 hours, and spray-dried to obtain a filler with a three-dimensional interpenetrating network structure.
[0010] Furthermore, the photoinitiator is selected from 2-hydroxy-2-methylphenylacetone.
[0011] Furthermore, the silane coupling agent is selected from γ-glycidoxypropyltrimethoxysilane.
[0012] Furthermore, the moisture-curing polyetheramine has an amine value of 300-350 mg KOH / g.
[0013] Furthermore, the borate ester crosslinking agent is selected from sodium tetraborate complex and organoboroate ester; the sodium tetraborate complex is sodium tetraborate and glycerol in a mass ratio of 3.5:1; the organoboroate ester is trimethyl borate.
[0014] Furthermore, the preparation method of the hydrophobically modified graphene oxide is as follows: graphene oxide and perfluorooctyltriethoxysilane are reacted in toluene at a mass ratio of 1:5 under reflux at 70-90°C for 5-6 hours, followed by centrifugation and drying. The water contact angle of the hydrophobically modified graphene oxide is ≥130°.
[0015] By adopting the above technical solution, bisphenol F epoxy resin in component A serves as the main resin, providing basic mechanical properties and corrosion resistance; dynamically disulfide bond modified polysulfide rubber serves as the core self-healing functional unit and toughening agent, introducing a reversible dynamic disulfide bond network to endow the coating with the ability to heal cracks after damage through the breaking and recombination of disulfide bonds. It can be prepared by reacting liquid polysulfide rubber with disulfide compounds such as 4,4'-diaminodiphenyl disulfide; boron nitride in the boron nitride nanosheet and silicon carbide nanowire hybrid filler provides high thermal conductivity, which helps to conduct the polymerization heat rapidly and achieve uniform curing, while silicon carbide nanowires provide high hardness and stability. The synergistic effect and three-dimensional interpenetrating network structure formed by the two can significantly improve the comprehensive physical properties of the coating; a photoinitiator is used to initiate the cationic polymerization of epoxy resin under ultraviolet light irradiation to achieve rapid surface curing; and a silane coupling agent is used to improve the interfacial compatibility and adhesion between the resin matrix and filler, as well as between the coating and the substrate.
[0016] The moisture-curing polyetheramine in component B acts as a moisture curing agent, reacting with the epoxy groups in component A in the presence of moisture (from ambient humidity or underwater environment) to achieve low-temperature, deep curing of the coating. The borate ester crosslinking agent can act as an auxiliary crosslinking agent to further enhance the density and stability of the cured network, or introduce dynamic borate ester bonds to synergistically improve the toughness or self-healing properties of the material. The hydrophobically modified graphene oxide, through hydrophobic treatment, achieves a water contact angle of ≥130°, forming a highly efficient hydrophobic barrier in the coating, effectively blocking the penetration of water molecules and corrosive media, and improving the corrosion resistance and underwater stability of the coating.
[0017] This application mixes component A and component B in a specific ratio, which helps to achieve the best balance of the functions of each component and the ideal curing effect.
[0018] The self-healing function of this invention mainly relies on the dynamically modified polysulfide rubber with disulfide bonds introduced in component A. The disulfide bonds (-SS-) contained in the polysulfide rubber segments are dynamic covalent bonds. Under specific conditions (such as moderate heating to 50°C, or slow reactions even at room temperature in some systems), these bonds can break and recombine, or exchange with other disulfide bonds. When the coating is subjected to external forces that cause cracks or scratches, the disulfide bonds at the crack interface break. Through external energy input (such as heat) or the movement of the polymer chain segments themselves, the broken disulfide bonds have the opportunity to reform, or exchange with adjacent intact disulfide bonds, thereby rebridging and healing the crack interface, restoring the structural integrity and some mechanical properties of the material. This invention achieves high self-healing efficiency by optimizing the structure and content of the polysulfide rubber.
[0019] Secondly, the present invention provides a method for preparing a light-wet dual-curing underwater epoxy coating with self-healing function, which is achieved by the following technical solution.
[0020] A method for preparing the above-mentioned self-healing light-wet dual-curing underwater epoxy coating includes the following steps: Preparation of component A: Bisphenol F type epoxy resin and dynamically disulfide bond modified polysulfide rubber were premixed at 50°C for 30 minutes; then boron nitride nanosheets and silicon carbide nanowire hybrid fillers, photoinitiators and silane coupling agents were added and dispersed to a fineness ≤15μm; Preparation of component B: Moisture-curing polyetheramine, borate ester crosslinking agent and hydrophobically modified graphene oxide are mixed and ultrasonically dispersed for 1 hour to form a moisture-responsive network.
[0021] Thirdly, the present invention provides a method for constructing a light-wet dual-curing underwater epoxy coating with self-healing function, which is achieved by the following technical solution.
[0022] A method for applying the above-mentioned self-healing, light-wet dual-curing underwater epoxy coating includes the following steps: a. Mix component A and component B evenly according to the specified ratio; b. Apply the mixture to the surface of the substrate; c. Expose the coated layer to ultraviolet light to trigger photocuring; d. Continue deep moisture curing of the coating in an ambient or underwater environment until fully hardened.
[0023] Furthermore, in step b, the substrate surface is pre-treated with appropriate surface treatment, including rust removal and cleaning.
[0024] Furthermore, in step c, the ultraviolet light irradiation conditions are: wavelength 365nm, light intensity 400-500mW / cm².2 Irradiation time: 30 seconds.
[0025] By adopting the above technical solution, the coating system of the present invention employs a unique light-wet dual curing mechanism: Photocuring stage: After mixing components A and B in the specified ratio and coating the substrate surface, ultraviolet light irradiation is immediately applied. The photoinitiator in component A absorbs ultraviolet light energy and decomposes to generate active cations or free radicals, which in turn initiate rapid ring-opening polymerization of the epoxy groups. This process allows the coating surface to dry rapidly in a very short time (e.g., within 30 seconds) and form preliminary strength and shape, making it ideal for rapid underwater positioning and initial fixation, reducing the impact of water flow erosion.
[0026] Moisture curing stage: Light curing mainly acts on the surface and near-surface areas of the coating. For deeper layers of the coating or areas inaccessible to light, curing relies on the moisture-curing polyetheramine in component B. The active amine groups in the polyetheramine molecule can undergo nucleophilic addition reactions with unreacted epoxy groups in component A in the presence of ambient moisture or underwater water, forming a stable three-dimensional cross-linked network structure. This process typically lasts for several hours at room temperature (e.g., 2-4 hours) to ensure complete and dense curing of the entire coating (including deeper layers).
[0027] This light-moisture dual curing mechanism combines the speed of light curing with the depth of moisture curing, effectively overcoming the limitations of a single curing method.
[0028] This application has the following beneficial effects.
[0029] (1) Efficient and rapid curing with deep curing: Through the cleverly designed light-wet dual curing mechanism, the material of the present invention can achieve rapid surface drying within 30 seconds under ultraviolet light irradiation, meeting the requirements of rapid underwater operation; at the same time, the subsequent moisture curing process can ensure that the coating is completely cross-linked and cured in depth within 2-4 hours. The total curing time (e.g., 4 hours) is significantly shortened compared with the traditional wet curing system (e.g., the comparison sample 3M DP420 requires 6 hours) (e.g., efficiency is increased by about 33%), overcoming the limitations of single curing methods in terms of speed and depth.
[0030] (2) Excellent self-healing function: This invention innovatively introduces dynamically disulfide bond-modified polysulfide rubber, endowing the coating with significant self-healing ability. Experiments show that after scratches occur on the coating, heating at 50°C for 30 minutes significantly heals the scratches, making them almost invisible, while traditional epoxy coatings (such as 3M DP420) do not possess this function. This greatly extends the service life of the coating in harsh marine environments and reduces maintenance costs.
[0031] (3) Significantly improved underwater adhesion performance: Through optimized formulation design, especially the effective use of silane coupling agents and the good matching of components A and B, the coating of this invention exhibits excellent adhesion to substrates such as metals in underwater environments. Example data shows that its underwater adhesion to steel can reach 4.8 MPa, which is up to 72% higher than that of commercially available high-performance underwater epoxy coatings (such as 3M DP420's 2.8 MPa), ensuring the reliability of the coating for long-term underwater service.
[0032] (4) Enhanced thermal conductivity: By introducing a specific ratio of boron nitride nanosheets and silicon carbide nanowires as hybrid fillers, the coating achieves good thermal conductivity (e.g., thermal conductivity ≥ 5 W / m·K, 5.3 W / m·K in the example), which is beneficial for the rapid dissipation of polymerization heat and uniform stress distribution.
[0033] (5) Excellent hydrophobicity and impermeability: The addition of hydrophobically modified graphene oxide in component B endows the coating surface with excellent hydrophobicity (e.g., water contact angle ≥130°). This highly hydrophobic surface can effectively block the penetration of water and corrosive media (e.g., chloride ions), thereby significantly enhancing the long-term anti-corrosion protection effect and underwater stability of the coating.
[0034] (6) Excellent comprehensive performance and application prospects: This invention combines multiple advantages such as rapid curing, self-healing, high adhesion, high thermal conductivity and strong hydrophobicity. It is particularly suitable for harsh marine engineering environments, such as rapid repair of deep-sea pipelines, structural reinforcement of offshore platforms, corrosion prevention and repair of underwater parts of ships, etc., and has broad application prospects. Detailed Implementation
[0035] The present patent application will be further described below with reference to the embodiments. Unless otherwise specified, the materials used in the preparation process in the following embodiments have not undergone further processing and have been commercially available.
[0036] The bisphenol F type epoxy resin 170 used in the following embodiments of the present invention was purchased from Shandong Deyuan Epoxy Technology Co., Ltd. The moisture-curing polyetheramine 8100 used in the following embodiments of the present invention was purchased from Wanhua Chemical Group Co., Ltd. The sodium tetraborate complex S102366 used in the following embodiments of the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The graphene oxide ADO1 used in the following embodiments of the present invention was purchased from Zhonghua Donghua Anhui New Materials Co., Ltd.
[0037] Example 1: Preparation of a self-healing, light-wet dual-curing underwater epoxy coating Preparation of component A Raw material composition: Bisphenol F type epoxy resin: 100g.
[0038] Dynamically disulfide-modified polysulfide rubber: 25g. Its preparation method is as follows: 100g of liquid terminal mercapto polysulfide rubber (JLY-124) was mixed with 30.8g of 4,4'-diaminodiphenyl disulfide (analytical grade), and 6g of N,N-dimethylformamide (DMF) was added as a solvent to reduce viscosity. The mixture was mechanically stirred for 4 hours under nitrogen protection at 70℃. After the reaction was completed, DMF was removed by vacuum distillation to obtain a pale yellow, viscous liquid dynamically disulfide-modified polysulfide rubber.
[0039] Boron nitride nanosheets and silicon carbide nanowire hybrid filler (BN / SiC): 15g. The preparation method is as follows: 5g of hexagonal boron nitride nanosheets and 10g of β-silicon carbide nanowires were added to 100mL of anhydrous ethanol and treated in an ultrasonic disperser for 2 hours to form a uniform suspension. Subsequently, a small spray dryer was used to prepare the hybrid filler, with the inlet temperature set at 180℃ and the outlet temperature at 100℃. The dried powder was collected as the BN / SiC hybrid filler.
[0040] Photoinitiator (2-hydroxy-2-methylphenylacetone): 4g.
[0041] Silane coupling agent (γ-glycidoxypropyltrimethoxysilane): 3g.
[0042] Preparation steps: 100g of bisphenol F epoxy resin and 25g of the dynamically disulfide bond modified polysulfide rubber prepared above were placed in a reactor equipped with a mechanical stirrer and a heating mantle. The mixture was premixed at 50°C and 200 rpm for 30 minutes until homogeneous. After the premix cooled slightly to room temperature, 15g of BN / SiC hybrid filler, 4g of photoinitiator, and 3g of silane coupling agent were added sequentially, and the mixture was stirred at low speed for another 15 minutes to achieve initial mixing. The mixture was then transferred to a three-roll mill, and the roller gap was adjusted for repeated grinding until the slurry fineness, as measured by a scraper fineness gauge, was ≤15μm. The ground slurry, known as component A, was collected and sealed for later use.
[0043] Preparation of component B Raw material composition: Moisture-curing polyetheramine: 60g.
[0044] Borate ester crosslinking agent (sodium tetraborate complex: the mass ratio of sodium tetraborate and glycerol is 3.5:1): 12g.
[0045] Hydrophobically modified graphene oxide: 8g. The preparation method is as follows: 1g of dry graphene oxide powder was dispersed in 100mL of toluene and ultrasonically dispersed for 30 minutes. Then, 5g of perfluorooctyltriethoxysilane was added, and the mixture was refluxed with magnetic stirring in an oil bath at 80℃ for 6 hours under nitrogen protection. After the reaction, the mixture was naturally cooled to room temperature, and the product was centrifuged (8000rpm, 10 minutes). It was then washed several times alternately with ethanol and deionized water to remove unreacted FOTS and byproducts. Finally, it was dried in a vacuum drying oven at 60℃ for 12 hours to obtain hydrophobically modified graphene oxide powder. The static contact angle of water droplets on its compressed surface was ≥130°.
[0046] Preparation steps: 60g of moisture-curable polyetheramine, 12g of borate ester crosslinking agent, and 8g of the hydrophobically modified graphene oxide powder prepared above were added to a clean, dry container and initially stirred with a glass rod. Then, the mixture was ultrasonically dispersed for 1 hour using a probe-type ultrasonic instrument (200W power, pulse mode with 5 seconds on, 5 seconds off), while the container was cooled in an ice-water bath to prevent localized overheating. Ensure uniform dispersion of all components to obtain component B, which was then sealed and stored for later use.
[0047] Application and curing of light-wet dual-curing underwater epoxy coatings a. Mixing: Before application, accurately weigh the required amounts of component A and component B according to a mass ratio of 2:1. For example, weigh 20g of component A and 10g of component B. At room temperature, use a spatula or small mixer to quickly and thoroughly mix the two in a clean container until the mixture is uniform in color and free of obvious streaks or lumps.
[0048] b. Coating: Immediately apply the well-mixed coating to the pretreated substrate surface. The substrate is a Q235 steel plate, 50mm × 50mm × 2mm in size, sandblasted to Sa2.5 grade, and cleaned and dried with anhydrous ethanol. Use a doctor blade to control the dry film thickness of the coating to 200μm.
[0049] c. UV Curing: Immediately place the coated steel plate sample in a UV curing chamber (or use a handheld UV lamp), employing an LED UV light source with a center wavelength of 365nm. Adjust the distance of the light source to ensure the light intensity on the sample surface reaches 500mW / cm². 2 Irradiate continuously for 30 seconds to complete the light curing of the coating surface.
[0050] d. Moisture Curing: After photocuring, place some samples in a standard laboratory environment (temperature 23±2℃, relative humidity 50±5%), and partially immerse some samples in a container filled with deionized water (or simulated seawater) for moisture / underwater curing. After 4 hours of treatment, the coating reaches its final mechanical properties.
[0051] Performance Tests and Results (1) Underwater adhesion test: Following ASTM D4541 (pull-out method), the coating from Example 1 was applied to the end face of a sandblasted steel pull-out head (20 mm in diameter) and bonded to a steel plate. After UV curing and moisture curing for 24 hours, the bonded sample was completely immersed in simulated seawater for 7 days. Subsequently, a portable pull-out adhesion tester was used at a loading rate of 1 MPa / s. The tensile force at failure and the failure mode were recorded.
[0052] Results: The average underwater adhesion of the coating prepared in Example 1 was 4.8 MPa, and the failure mode was mainly cohesive failure.
[0053] (2) Self-healing test: On the fully cured coating (2 mm thick), a 5 mm long and 1 mm deep scratch was made with a sharp scalpel. The initial morphology of the scratch was recorded (optical microscope). The scratched sample was then placed in an oven at 50 °C and heated for 30 minutes. After being removed and cooled to room temperature, the healing of the scratch was observed again.
[0054] Results: After heating at 50°C for 30 minutes, the scratches on the coating prepared in Example 1 were significantly healed and almost invisible.
[0055] (3) Thermal conductivity test: The thermal conductivity was tested using a laser flash thermal conductivity meter. The coating was made into a circular sample with a diameter of 12.7 mm and a thickness of 1 mm, and tested after it was completely cured.
[0056] Results: The thermal conductivity of the cured product in Example 1 was 5.3 W / m·K.
[0057] (4) Observation of curing time (refer to GB / T 1728-2020): The coating of Example 1 was cured at 365nm UV and 500mW / cm 2 It will be surface dry after 30 seconds of irradiation. It will then be fully dry after 4 hours of moisture curing, with a total curing time (to reach the final design strength) of approximately 4 hours.
[0058] (5) Hydrophobicity test: The static contact angle of a water droplet (5μL) on a fully cured flat coating surface was measured using a contact angle meter (OCA series, DataPhysics Instruments). At least 5 different locations were measured for each sample, and the average value was taken.
[0059] Results: The average water contact angle of the cured coating surface in Example 1 was 135° (≥130° requirement).
[0060] Comparative example: Commercially available underwater epoxy coating (3M DP420) Materials: Commercially available two-component epoxy structural adhesive 3M DP420.
[0061] Application and curing: Mix components A and B according to the mixing ratio recommended in the product instructions (usually 2:1 volume ratio or mass ratio), apply to the same pretreated steel plate, and cure at room temperature (23±2℃) and standard humidity (50±5%) or underwater.
[0062] Performance Tests and Results: (1) Underwater adhesion: According to relevant literature or product characteristics, its underwater adhesion under similar conditions is about 2.8 MPa.
[0063] (2) Self-healing function: This type of traditional epoxy resin system usually does not have a self-healing function.
[0064] (3) Curing time: It takes 4 hours to reach operational strength and 12 hours to fully cure (reach maximum strength) (6 hours is taken as the benchmark for initial full curing).
[0065] (4) Thermal conductivity: The thermal conductivity of traditional unfilled epoxy resin is usually low, ranging from 0.2 to 0.3 W / m·K.
[0066] Comparative analysis of Example 1 and the comparative example: (1) Underwater adhesion: Example 1 (4.8 MPa) is much higher than the comparative example (2.8 MPa), with an increase of (4.8-2.8) / 2.8 × 100% ≈ 71.4%.
[0067] (2) Self-healing ability: Example 1 has a scratch self-healing function, while the comparative example does not have this function.
[0068] (3) Curing time: The total curing time of Example 1 is about 4 hours. The comparative example requires 6 hours or longer to achieve a similar degree of curing. The curing efficiency of Example 1 is improved by about (6-4) / 6 × 100% ≈ 33.3%.
[0069] (4) Thermal conductivity: Example 1 (5.3 W / m·K) is much higher than the 0.2-0.3 W / m·K of traditional epoxy, showing excellent thermal conductivity.
[0070] (5) Hydrophobicity: Example 1 (135°) exhibits excellent hydrophobicity, which helps to enhance impermeability and corrosion resistance.
[0071] The performance metrics of the embodiments and comparative examples are shown in the table below: The above comparison clearly demonstrates that the light-wet dual-curing underwater epoxy material provided by this invention is significantly superior to traditional or commercially available epoxy material systems in terms of rapid curing, self-healing ability, underwater adhesion, and thermal conductivity, and has obvious innovative and practical value.
[0072] This invention enables the underwater coating to achieve both rapid surface curing and complete deep curing, meeting the requirements for rapid construction and final performance. It endows the underwater epoxy coating with highly efficient self-healing capabilities to cope with mechanical damage during service and extend its service life. While achieving the above functions, this invention also ensures that the coating possesses excellent underwater adhesion, heat resistance, hydrophobicity, and long-term corrosion resistance. Therefore, due to its unique comprehensive performance, this coating has broad application prospects in offshore platform structure repair, subsea pipeline leak sealing, rapid underwater ship repair, hydraulic structure crack repair, and other fields requiring rapid and reliable bonding and protection in humid or even underwater environments.
[0073] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A light-wet dual-curing underwater epoxy coating with self-healing function, characterized in that: It includes component A and component B, with a mass ratio of component A to component B of (1.5-3.5):1; Component A comprises the following raw materials in parts by weight: Bisphenol F type epoxy resin: 100 parts; Dynamic disulfide bond modified polysulfide rubber: 20-30 parts; Boron nitride nanosheets and silicon carbide nanowire hybrid filler: 10-20 parts; Photoinitiator: 3-5 parts; Silane coupling agent: 2-4 parts; Component B comprises the following raw materials in parts by weight: Moisture-curing polyetheramine: 50-70 parts; Boron ester crosslinking agent: 10-15 parts; Hydrophobically modified graphene oxide: 5-10 parts.
2. The underwater epoxy coating with self-healing function that undergoes both light and wet curing as described in claim 1, characterized in that: The sulfur content of the dynamically disulfide bond modified polysulfide rubber is 15-20%. The preparation method of the dynamically disulfide bond modified polysulfide rubber is as follows: liquid polysulfide rubber and 4,4'-diaminodiphenyl disulfide are mixed in a molar ratio of 1:(1~2) and reacted at 60-80℃ for 2~6 hours to generate a prepolymer containing dynamic disulfide bonds.
3. The underwater epoxy coating with self-healing function that undergoes both light and wet curing as described in claim 1, characterized in that: The preparation method of the boron nitride nanosheets and silicon carbide nanowire hybrid filler is as follows: boron nitride nanosheets and silicon carbide nanowires are dispersed in ethanol at a mass ratio of 1:2, ultrasonically treated for 2-4 hours, and spray dried to obtain a filler with a three-dimensional interpenetrating network structure.
4. The self-healing, light-wet dual-curing underwater epoxy coating according to claim 1, characterized in that: The photoinitiator is 2-hydroxy-2-methylphenylacetone.
5. The self-healing, light-wet dual-curing underwater epoxy coating according to claim 1, characterized in that: The silane coupling agent is selected as γ-glycidoxypropyltrimethoxysilane.
6. The self-healing, light-wet dual-curing underwater epoxy coating according to claim 1, characterized in that: The borate ester crosslinking agent is selected from sodium tetraborate complex and organic borate ester; the sodium tetraborate complex is sodium tetraborate and glycerol in a mass ratio of 3.5:1; the organic borate ester is trimethyl borate.
7. The self-healing, light-wet dual-curing underwater epoxy coating according to claim 1, characterized in that: The preparation method of the hydrophobic modified graphene oxide is as follows: graphene oxide and perfluorooctyltriethoxysilane are reacted in toluene at 70~90℃ for 5-6 hours in a mass ratio of 1:5, and then centrifuged and dried to obtain the product.
8. A method for preparing a self-healing, light-wet dual-curing underwater epoxy coating as described in any one of claims 1-7, characterized in that: Includes the following steps: Preparation of component A: Bisphenol F type epoxy resin and dynamically disulfide bond modified polysulfide rubber were premixed at 50°C for 30 minutes; then boron nitride nanosheets and silicon carbide nanowire hybrid fillers, photoinitiators and silane coupling agents were added and dispersed to a fineness ≤15μm; Preparation of component B: Moisture-curing polyetheramine, borate ester crosslinking agent and hydrophobically modified graphene oxide are mixed and ultrasonically dispersed for 1 hour.
9. A method for applying a self-healing, light-wet dual-curing underwater epoxy coating as described in any one of claims 1-7, characterized in that, Includes the following steps: a. Mix component A and component B evenly according to the specified ratio; b. Apply the mixture to the surface of the substrate; c. Expose the coated layer to ultraviolet light to trigger photocuring; d. Continue deep moisture curing of the coating in an ambient or underwater environment until fully hardened.
10. The construction method according to claim 9, characterized in that: In step c, the ultraviolet light irradiation conditions are: wavelength 365nm, light intensity 400-500mW / cm². 2 Irradiation time: 30 seconds.
Citation Information
Patent Citations
Underwater curable coating, underwater protective layer and application thereof
CN104745046A
Underwater curing paint and preparation method thereof
CN106752689A
Hydrophobic graphene solvent-free epoxy underwater curing coating and preparation method thereof
CN108192471A
Underwater curing coating comprising graphene oxide and preparation method
CN108250910A
Cited By
Carbon nano polymer repairing material for assisting in repairing speed reducer shaft and preparation method and repairing process of carbon nano polymer repairing material
CN122188493A
Self-repairing tread modification protectant and method of making
CN122356887A
Epoxy adhesive special for wet environment and preparation method and application thereof
CN122427635A
